Plastic flowers adding value to floriculture industry - Jain, Ritu; Kumar, Prabhat; Pinder, Rohit; Kumar, Raman; Janakiram, T. (Indian Horticulture, 2019)
Since time immemorial, flowers have been utilized by the mankind both for beauty and utility. The flowers are admired for their beauty, fragrance, colour, exquisite shape and some special traits. Most of them are used as loose and cut flowers, garlands, wreath, bouquets, arrangements, for fragrance essential oils, perfumes, dry flower, pot pourries etc. These are also used to gift on special occasions like birthday parties, weddings, religious ceremonies and funerals etc. Due to urbanization and industrialization, the land has become scarce and people cannot afford to grow these flowers to enjoy their charismatic beauty, therefore they have shifted towards the purchase of different categories of flowers like fresh flowers, potted flowers and artificial flowers (dry flowers and plastic flowers).